2020
DOI: 10.1007/s12192-019-01047-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an inducible HSP70 gene in Chilo suppressalis and expression in response to environmental and biological stress

Abstract: The highly conserved heat shock protein 70 (HSP70) contributes to survival at a cellular level and greatly enhances stress tolerance in many organisms. In this study, we isolate and characterize Cshsp702, which encodes an inducible form of HSP70 in the rice stem borer, Chilo suppressalis. Cshsp702 does not contain introns; the translational product is comprised of 629 amino acids with an isoelectric point of 5.69. Real-time quantitative PCR revealed that Cshsp702 was expressed at maximal levels in hemocytes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Cchsp11.0 and Cchsf expression increased at the 15 min time point in response to heat stress and then declined until another round of induction 2 h. The decreased expression of Cchsp11.0 at 30 min and 1 h may be related to the regulation of other HSPs [ 2 ], and the decline in Cchsf expression at these times may be related to the negative regulation of HSF by HSP. Previous studies showed that many small heat shock proteins have their maximum expression after 2 h of temperature treatment, such as Cshsp702 , Cshsp19.8 , Cshsp21.7b , Cshsp21.5 , which is consistent with our experimental results [ 1 , 23 ]. At 4 h, the expression of Cchsf decreased again, suggesting that HSF transcriptional activity is weakened somewhat over time [ 19 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Cchsp11.0 and Cchsf expression increased at the 15 min time point in response to heat stress and then declined until another round of induction 2 h. The decreased expression of Cchsp11.0 at 30 min and 1 h may be related to the regulation of other HSPs [ 2 ], and the decline in Cchsf expression at these times may be related to the negative regulation of HSF by HSP. Previous studies showed that many small heat shock proteins have their maximum expression after 2 h of temperature treatment, such as Cshsp702 , Cshsp19.8 , Cshsp21.7b , Cshsp21.5 , which is consistent with our experimental results [ 1 , 23 ]. At 4 h, the expression of Cchsf decreased again, suggesting that HSF transcriptional activity is weakened somewhat over time [ 19 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…C. suppressalis and C. chilonis were collected from a suburb of Yangzhou (32.39 °N, 119.42 °E) and reared under the laboratory conditions at 27 ± 1 °C, 60–70% RH and a 16:8 h (light/dark) photoperiod [ 2 ]. C. suppressalis larvae were reared on an artificial diet [ 1 ]. C. chilonis adults were supplied with a 10% honey/water solution and propagated using 5th instar larvae of C. suppressalis as hosts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chilo suppressalis (Walker) (Lepidoptera: Pyralidae) is a detrimental rice pest in southern Europe, northern Africa and widely distributed in China and other Asian countries ( Lu et al, 2013 ; Luo et al, 2014 ). Issues of pesticide residues, environmental pollution and pesticide poisoning have attracted the attention and stimulated the explore on new biological control methodologies such as the use of natural enemies ( He et al, 2013 ; Hong, 2015 ; Gao et al, 2019 ). Cotesia chilonis (Munakata) is the dominant parasitoid of C. suppressalis and occurs in southeastern and eastern Asia, regions where it has value as a biological control agent for C. suppressalis ( Huang, Wu & Ye, 2011 ; Wu et al, 2013 ; Pan et al, 2018 ) .…”
Section: Introductionmentioning
confidence: 99%